Eksplorasi Material Daun Lontar (Borassus Flabellifer L.) di Daerah Flores Timur - Hanifa, Zalfa; Triharini, Meirina; Malasan, Prananda; Puspita, Arianti; Taepoer, Raditya (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
Lontar is distributed in various areas of Indonesia, especially in East Nusa Tenggara (NTT). Over the past few years, lontar weaving in East Flores has experienced rapid development in various aspects. This research is conducted to analyze the dynamics that emerge in the community and formulate further stages of exploration by considering relevant aspects. This research used a mixed methods approach, first conducting qualitative research based on field observations in three villages in East Flores, and simple material exploration and experimentation. The results of this research are the design of a production system, a study of factors that influence the development of lontar material products and their impact on local communities, alternative product design, and an overview of the growth of local communities in Indonesia and how they can work together with other parties outside their region.